Procuring Pavement Management Data-Collection Services - Bennett, C. R. (2012)
Data are the foundation for any successful pavement management system (PMS). Without appropriate and relevant data, the PMS cannot be used to make sensible decisions. As data-collection technologies become more sophisticated, the trend is. away from agencies conducting in-house data collection towards contracting out these services. For this to be effective, it is necessary for the agency to ensure that it has an appropriate specification, good contract management procedures, and a robust quality assurance framework. The World Bank, having financed data-collection. activities for a number of projects, has recently prepared a generic terms of reference for procuring data-collection services that reflects its experience in a number of countries (Mallela 2007). This paper summaries the key issues encountered by the Bank, and how they can be addressed in procuring data-collection services.